PENGARUH KONSERVATISME AKUNTANSI PADA MANAJEMEN LABA - Sri Ruwanti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2017)
The result from Lin, Wu, Fang & Wun, (2014) show that the negative association between earnings management and institutional investor shareholdings. They find if corporate financial statements tend toward conservatism, institutional investor shareholdings could increase managers' incentive to manage earnings. Motivated from them, this study aims to analyze whether conservatism accounting has influence on earnings management. With use manufacture companies listed in Indonesia Stock Exchange (IDX) 2012-2015. The population of this study amounted 132 companies, where sample amounted 32 with sample selection criteria. I find that accounting conservatism has influence to earnings management. Keywords: Conversatism, earnings management